Review Evaluation of Steel Frame Improved with Bracing Systems Equipped with Yielding Dampers (Journal of Civil Engineering Researchers, 2020)
Structural control systems are used to reduce structural damage in earthquakes. These systems have developed significantlyover the last few decades. They can be broadly classified into three categories: 1) Passive control system in which structuresare equipped with devices that do not require an external energy source. 2) Active control systems in which the structures areequipped with processing and transmission sensors and in which there are devices that need an external energy source towork, and 3) Semi-active control system to change There are structural properties that require little external energy. In thepresent review article, we have tried to fully evaluate this field of study by evaluating four valid articles in the field ofevaluating the effects of energy consuming dampers in steel frames. The results of the studies showed that the presence ofvarious dampers including new submersible metal dampers, hybrid, viscoelastic, submersible strip wave and two-levelsubmersible torque has caused the performance indicators of the steel frame, including; Shear strength, displacement ofstructural floors, energy, hysterical performance (hysteresis curve), etc., which indicates the performance of the structure, hasbeen improved and in all evaluated indicators, the structure has increased the level of performance.
Keywords: Steel Frame; Damper; Yielding Brace; Passive Control; Hysteresis Curve.